2018
DOI: 10.1001/jamaophthalmol.2018.2986
|View full text |Cite
|
Sign up to set email alerts
|

Association of Uveal Melanoma Metastatic Rate With Stochastic Mutation Rate and Type of Mutation

Abstract: Importance: To understand the mechanisms of metastasis of uveal melanoma in order to advise patients and develop treatments for this tumor. Objective: The purpose of this study was to examine the stochastic properties of primary uveal melanoma including the mutation rate as a function of tumor size and metastatic rate relative to the type of mutation. Data sources, Study Selection, Main Outcome and Measures: We computed the mutation rate in different sized uveal melanomas using previously published large d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 44 publications
2
32
0
Order By: Relevance
“…Specific type of mutation and the Zimmerman effect. Our study of the time of metastatic uveal melanoma versus type of mutation 15 based on a large dataset 18 showed that uveal melanomas harboring BAP1 mutations account for metastases detected at 2 to 3 years, and that those with SF3B1 mutations account for metastases detected at 4 to 8 years after the primary tumor is diagnosed and treated. This helps explain the Zimmerman effect.…”
mentioning
confidence: 90%
See 4 more Smart Citations
“…Specific type of mutation and the Zimmerman effect. Our study of the time of metastatic uveal melanoma versus type of mutation 15 based on a large dataset 18 showed that uveal melanomas harboring BAP1 mutations account for metastases detected at 2 to 3 years, and that those with SF3B1 mutations account for metastases detected at 4 to 8 years after the primary tumor is diagnosed and treated. This helps explain the Zimmerman effect.…”
mentioning
confidence: 90%
“…This can be explained by the expansion phase in tumor growth: When a precursor lesion, such as a nevus, undergoes a mutational event in which it becomes a malignant neoplasm (melanoma), the mutation rate is higher than after the neoplasm is established and grows. 15 To summarize, as a melanoma initially forms, the proportion of metastasis-related mutant versus nonmutant cells in the tumor is slightly higher than when the melanoma further enlarges, although the larger the tumor, the greater the absolute number of metastasis-related mutant tumor cells.…”
mentioning
confidence: 95%
See 3 more Smart Citations